2015
DOI: 10.1128/aem.01035-15
|View full text |Cite
|
Sign up to set email alerts
|

Arcobacter butzleri, Arcobacter cryaerophilus, and Arcobacter skirrowii Circulation in a Dairy Farm and Sources of Milk Contamination

Abstract: Even though dairy cows are known carriers of Arcobacter species and raw or minimally processed foods are recognized as the main sources of human Arcobacter infections in industrialized countries, data on Arcobacter excretion patterns in cows and in milk are scant. This study aimed to identify potentially pathogenic Arcobacter species in a dairy herd and to investigate the routes of Arcobacter transmission among animals and the potential sources of cattle infection and milk contamination. A strategy of sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
4
40
0
1
Order By: Relevance
“…Very recently, water contamination of Arcobacter (80%) in a farm was documented with A. skirrowii (13%), A. butzleri (40%) and A. cryaerophilus (63%). Same Arcobacter species were isolated after two months from the water troughs which indicates the capacity to form biofilms or as a secondary bioformer (Giacometti et al 2015). This study also reported the presence of A. butzleri in oral cavity of cats.…”
Section: Epidemiology and Transmission In Animalssupporting
confidence: 58%
See 3 more Smart Citations
“…Very recently, water contamination of Arcobacter (80%) in a farm was documented with A. skirrowii (13%), A. butzleri (40%) and A. cryaerophilus (63%). Same Arcobacter species were isolated after two months from the water troughs which indicates the capacity to form biofilms or as a secondary bioformer (Giacometti et al 2015). This study also reported the presence of A. butzleri in oral cavity of cats.…”
Section: Epidemiology and Transmission In Animalssupporting
confidence: 58%
“…A study by Giacometti et al (2015) indicated absence of Arcobacter spp. in pigeon gut samples (47 numbers tested) and that these birds do not have any role in transmission of Arcobacter to cattle.…”
Section: Epidemiology and Transmission In Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…; Giacometti et al . ), in‐line milk filters (Serraino et al . ), cow and water buffalo milk (Scullion et al .…”
Section: Introductionmentioning
confidence: 99%